Analisis Kemampuan Membaca Al-Qur’an Dalam Perspektif Sosiologi Pengetahuan - Mahdali, Fitriyah (Universitas Islam Negeri Imam Bonjol Padang, 2020)
MAN 1 Malang is one of the formal educational institutions in Malang regency under the auspices of the Ministry of Religious Affairs. The vision and mission includes forming students who are religious and carry out religious activities in daily life. One indicator that must be met to become a religious individual is to be able to understand and carry out the contents contained in the holy book of the Qur'an. A necessity to be able to understand the contents of a person must be able to read it. With this background, this study focuses on three problems: (1) How to portray the ability of MAN students in reading the Qur'an, (2) What is the process of internalizing students in their environment, especially those who cannot read the Qur'an, and (3) How is the principal's effort in dealing with students who cannot read the Qur'an. This research is a study of the sociology of education. The method used in this research is descriptive qualitative, which is one type of research that aims to describe and understand certain phenomena. The approach used is the sociology of knowledge. Namely revealing a phenomenon using knowledge that develops in the wider community. The findings in this study are (1) Of the 952 students of MAN 1 Malang, there were 49 students who could not read the Qur'an. This phenomenon is contrary to the existing vision and mission. (2) The internalization process greatly affects the ability of students to read the Qur'an. These factors include family support, environmental conditions, family conditions and student internal factors. (3) Efforts made by MAN 1 Malang to succeed in its vision and mission are to hold a Qur'an reading guidance program for students who have not been able to.